Size distribution of vehicle emitted primary particles measured in a traffic tunnel. (October 2018) - Li, Xiang; Dallmann, Timothy R.; May, Andrew A.; Stanier, Charles O.; Grieshop, Andrew P.; Lipsky, Eric M.; Robinson, Allen L.; Presto, Albert A.
Abstract: Total and size-resolved concentrations and emission factors are used to compare fleet-averaged vehicle emissions in Pittsburgh, PA in 2002 and 2014. Winter-time traffic tunnel measurements acquired using dual scanning mobility particle sizers (SMPS) over the size range 3–500 nm form the key input for the analysis. Size-resolved mass emission factors were calculated assuming a nanoparticle aggregate model. The ultrafine particle (<30 nm) emissions of diesel vehicles significantly dropped from 2002 to 2014. In the 2014 study, a thermodenuder (TD) was deployed together with the SMPS to measure emissions of non-volatile particles. After evaporation at 250 °C inside the TD, the median diameter of the number-size distribution shifted from 16 nm to ∼7 nm. The total particle number decreased significantly (69%) after evaporating inside the TD, indicating that vehicle emitted particles may be largely externally mixed and that a large fraction of these particles may be purely composed of volatile components. Based on the SMPS-TD measurements, we report a size-resolved volatile-to-non-volatile-component-ratio for vehicle emitted particles. It shows that smaller particles (10–60 nm) emitted by vehicles are dominantly (over 75%) composed of volatile components. We also apportioned the size-resolved particles and non-volatile particle mass and number emission factors for both gasoline and diesel vehicles. Diesel vehicles emitted significantly more ultrafine particles and non-volatile particles than gasoline vehicles. Graphical abstract: Image 1 Highlights: Size-resolved particle emission factors for on-road vehicles show that particles are largely externally mixed. Particles smaller than 50 nm are dominated by volatile components. Emissions from gasoline and diesel vehicles have been reduced since 2002, with larger reductions in diesel emissions.